Efeitos do treinamento de força e da reposição hormonal no mecanismo de ação de irisina de ratas ovariectomizadas - Magosso, Natalia Santanielo Silva (2015)
The reduction in estrogen concentration, a physiological situation of the female aging, in addition to changes such as increased risk of coronary heart disease, loss of muscle mass and loss of bone mass is also associated with changes in fat composition. Studies from our research laboratory show that ST produces benefits such as increasing the amount of lean body mass, glucose control and reduced lipid content in the liver and muscles. Irisin is known to be a potential therapeutic target in metabolic diseases, including obesity, and its molecular mechanisms are initiated through exercise. Objective: To investigate the effects of ST and HR in plasma levels of Irisin, gene and protein expression of factors involved in the action of Irisin in ovariectomized rats. Methods: 66 rats Holtzman were randomly divided into six groups: 1) Sham-Sed; 2) Sham-ST; 3) Ovx-Sed; 4) Ovx-ST; 5) Ovx-Sed-RH; 6) Ovx-ST-RH. The ST protocol required the animals to climb a 1.1 m-long vertical ladder with weights atteched to their tails. Each session consisted of 4 to 8 climbs with 2 minutes interval between climbing, performed once every three days for 12 weeks. Analyses of PGC1-α mRNA expression, and FNDC5 and UCP1 were performed by RT-PCR ΔΔCt method, protein expression analysis of FNDC5 and UCP1 were performed by the Western blotting technique, Irisin and 17β-estradiol levels were determined by ELISA. Results: Our results show that the Sham, Ovx and HR groups who underwent 12 weeks of ST had a higher expression of the Irisin action mechanism, with higher mRNA expression of PGC-1α in the gastrocnemius muscle, increased protein expression FNDC5, higher Irisin concentration in the plasma and increased protein expression of UCP1 in mesenteric fat. Conclusion: Ovariectomized rats had lower circulating concentration Irisina, which promotes browning of white adipose tissue, however, the ST for 12 weeks was an effective intervention strategy to contain higher circulating concentration of Irisin in intact and ovariectomized rats. And the TF associated with RH was an effective intervention strategy to contain higher circulating concentration of Irisin in ovariectomized.